Penyuluhan Hukum “Meningkatkan Kesadaran Hukum Masyarakat Dalam Bermedia Sosial di Desa Keraswetan” - Taufiq Yuli Purnama; Sigit Sapto Nugroho; Anik Tri Haryani; Retno Iswati (JURNAL DAYA-MAS, 2024)
The purpose of this Community Service is to provide understanding and legal awareness for the community in using social media. Legal counselling was conducted in Keraswetan village, Geneng sub-district, Ngawi district and other legal issues related to the conditions of each village. The use of social media must be realised by the community in order to have a positive impact on the progress of society. In this almost digital age, there are still many violations of social media. The method used in this activity is in the form of a directed discussion which begins with counselling/lecture then continued with direct questions and answers. The participants were community members, especially women and local community leaders. The community does not fully understand the use of social media. Through this legal counselling activity, every citizen is expected to be able to utilise existing social media for positive and beneficial interests, and to be wise in social media. By understanding the law, it is expected that there will be an increase in public legal awareness.